Mind matters:a critical look at Malaysia’s postnatal depression policy for women’s mental health - Alimuddin, Aishah Siddiqah; Mohd Shukor, Nuur Asyikin; Soh, Shean Yih; Suainbon, Rosnadia; Mahmud, Asma Assa'edah; Abdul Samad, Farah Deena; Ismail, Nurazah; Asiff, Muna Hamiza (Mary Ann Liebert, 2023)
Introduction: This policy brief examines the national health and action plans, laws and regulations, public health policies, and clinical practice guidelines in Malaysia on postnatal depression (PND). Methods: We examined and included 13 documents for the presence or lack of a statement of intent and/or actions related to caring for women at risk for or experiencing PND. Results: Although PND is actively researched and included in the clinical practice guidelines, no other policy documents mention PND. Conclusion: General recommendations to address this matter include channeling resources into developing care for PND, increasing advocacy work to reduce stigma, setting up appropriate training pathways for health care providers, and creating more roles and user-friendly modules for local volunteers to deliver mental health interventions